Adopsi Pembayaran Mobile dan Peningkatan Konsumsi Rumah Tangga: Peran Mediasi Inklusi Keuangan Digital di Indonesia - Muthia Salsabillah Rusmulya; Goso Goso; Duriani Duriani (Universitas Nusantara PGRI Kediri, 2026)
This study aims to analyze the mediating role of digital financial inclusion in the relationship between mobile payment adoption and increased household consumption in Indonesia. The method used is a quantitative approach with an explanatory research design, involving 400 respondents spread across various regions of Indonesia and selected through stratified random sampling. Data were collected through online and offline questionnaires, then analyzed using Structural Equation Modeling (SEM) with bootstrapping techniques. The results show that mobile payment adoption has a positive and significant effect on digital financial inclusion (β = 0.582; t = 12.516; p < 0.001), digital financial inclusion has a positive and significant effect on household consumption (β = 0.561; t = 9.461; p < 0.001), and mobile payment adoption has a direct effect on household consumption (β = 0.249; t = 4.816; p < 0.001). Furthermore, digital financial inclusion was shown to partially mediate the relationship between mobile payment adoption and household consumption, with an indirect effect coefficient of 0.326 (VAF = 56.7%). This finding implies that a strategy to expand digital financial inclusion based on mobile payments is an effective policy instrument for driving increased domestic consumption and national economic growth.